Kajian Musikologis: Program Super SightReading Secrets Howard Richman Dalam Pengembangan Keterampilan Primavista Pianis - Widyatama Putra, Zakarias Aria; Sagala, Mastri Dihita (TACET Jurnal Pendidikan dan Kajian Seni, 2022)
This musicological study discusses Howard Richman's super sight-reading secrets program on the development of primavista pianist skills. Looking at the two elements of musicology, the research method used examines qualitatively with a musicological approach (theoretical and analytical). The process of collecting data using observation techniques, interviews, literacy studies, and documentation. The data that has been taken is then carried out by the process of selection, adaptation or processing, and delivery. Data validity uses source triangulation. The results of the study obtained theoretically, Howard Richman conveyed three basic things as the development of primavista pianist skills, namely: 1) pitch accuracy; 2) rhythmic; and 3) fingering. Analystically, Howard Richman's reasons for wanting to spread sight reading development alternatives for pianists are based on personal experience and sight reading processes, which consist of: 1) visual; 2) electro/chemical; 3) kinetic; and 4) aural. The process involves the eyes to see the notes, electro/chemical which involves the mind to control the nerves and instruct the muscles to play the notes which are then heard by the ears. The results of discussions with both novice and advanced pianists were in accordance with this study and found a real implementation of the program from Howard Richman, namely that it can be used easily and the implementation of exercises is effective and efficient..